A rational cubic spline technique for preserving the positivity of data - Al-Abbasi, Anas Khalaf Faris (Institute of Engineering Mathematics, 2016)
This research addresses the problem of preserving positivity of curves and surfaces. It has three goals that are to investigate some existing positivity preserving algorithms for curve and surface; to develop positivity preserving algorithms using rational cubic spline technique for curves and surfaces; to discuss some of the current positivity - preserving algorithms.